Ethnoscience Studies in Songket Sasak Cloth Motifs: Prospective Science Teacher Perceptions - Agus Muliadi; Suhirman Suhirman; M. Khairul Wazni; M. Yamin; Yusran Khery (Jurnal Penelitian Pendidikan IPA, 2022)
The aims of this study were to explore the perceptions of prospective science teachers towards ethnoscience studies in the songket cloth motif of the sasak tribe. This exploratory research conducted in three education study programs namely Biology, Chemistry, and Physics Education with 53 prospective science teachers involved as research subject. Closed questionnaire with likert scale and expertly validated applied for data collection. The data were analyzed by quantitative descriptive statistics, Anova test and t-test inferential statistics. The results showed that (1) perception of prospective science teachers has an average score in the "Good" category in terms of gender, regional origin, and study program; (2) there were no significant differences in the perceptions in male and female prospective science teacher based on t-test significance value of 0,455 > 0,05; (3) there were no significant difference in prospective science teacher’s perception refer to origin (native Lombok and non-native) based on t test significance value of 0,466 > 0,05; (4) there were no significant difference in the perception of prospective science teachers in the biology, chemistry, and physics education study program based on Anova's significance value of 0,423 > 0,05.